Review of Swirski, Peter. 2015. American Political Fictions: War on Errorism in Contemporary American Literature, Culture, and Politics. US: Palgrave Macmillan. 214 pages. ISBN: 978-1-349-70461-3 - Xiong, Lian (International Journal of English Studies, 2018)
Review of Swirski, Peter. 2015. American Political Fictions: War on Errorism in Contemporary American Literature, Culture, and Politics. US: Palgrave Macmillan. 214 pages. ISBN: 978-1-349-70461-3